2016
DOI: 10.1002/jcop.21878
|View full text |Cite
|
Sign up to set email alerts
|

Sense of community and life satisfaction in Chinese older adults: Moderating roles of personal and partner resilience

Abstract: From an ecological perspective, this study aimed to examine the relationship between a sense of community and life satisfaction as moderated by personal resilience and partner resilience among Chinese older adults. Using a cross‐sectional design, a total of 258 Chinese couples (age range 60–97 years) completed measures related to sense of community, resilience, and life satisfaction. The results showed that (a) sense of community was positively associated with life satisfaction after controlling for personal r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 39 publications
0
27
0
1
Order By: Relevance
“…The direct effect of sense of community on life satisfaction and the mediating effect of psychological resilience on the relationship between sense of community and life satisfaction confirmed the positive effects of sense of community on people's psychological status (Pretty, Bishop, Fisher, & Sonn, ; Prezza, Amici, Roberti, & Tedeschi, ; Zhang et al, ). McMillan and Chavis () argued that if people had stronger sense of community, they would feel that they had more influence on their immediate environment.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…The direct effect of sense of community on life satisfaction and the mediating effect of psychological resilience on the relationship between sense of community and life satisfaction confirmed the positive effects of sense of community on people's psychological status (Pretty, Bishop, Fisher, & Sonn, ; Prezza, Amici, Roberti, & Tedeschi, ; Zhang et al, ). McMillan and Chavis () argued that if people had stronger sense of community, they would feel that they had more influence on their immediate environment.…”
Section: Discussionmentioning
confidence: 62%
“…Items were designed to refer respondents’ neighbourhood and used a 5‐point Likert‐type response (1 = strongly disagree to 5 = strongly agree ). The BSCS was used in Chinese context and found to be reliable (Huang, Tan, & Liu, ; Zhang et al, ). The Cronbach's alpha of the scale was 0.94 in the current research.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings from these studies reveal that PSOC and subjective well-being were significantly and positively associated among adults from a range of countries (the United States, Italy, China), from variously sized townships, and controlling for other factors such as resilience and senior services (Davidson & Cotter, 1991;Ditchman, Keegan, Batchos, Haak, & Johnson, 2017;Hilbrecht, Lero, Schryer, Mock, & Smale, 2017;Mak, Cheung, & Law, 2009;Moscato, Novara, Hombrados-Mendieta, Romano, & Lavanco, 2014;Ng & Fisher, 2016;Obst & Tham, 2009;Prezza et al, 2001;Prezza & Costantini, 1998;Ramos, Suarez, Leon, & Trinidad, 2017;Zhang, Yu, Zhang, & Zhou, 2017;Zhang, Zhang, Zhou, & Yu, 2018). More specifically, PSOC and subjective well-being demonstrated a positive relationship among adults in the United States (Davidson & Cotter, 1991); residents in various communities in Italy (Prezza et al, 2001;Prezza & Costantini, 1998); Chinese residents in Hong Kong and Beijing (Mak et al, 2009;Ng & Fisher, 2016;Zhang et al, 2017; Hispanic immigrants in rural Nebraska (Ramos et al, 2017); migrants in Italy (Moscato et al, 2014); and churchgoers in Australia (Obst & Tham, 2009), where the influence dimension of PSOC (SCI; was specifically related to life satisfaction (SWLS;Diener et al, 1985).…”
Section: Adult Populationsmentioning
confidence: 99%
“…Older adults commonly identify community participation and engagement, social interactions and connectedness, and "neighborliness" as central to AFCs (Feldman and Oberlink, 2003;Emlet and Moceri, 2012;Cho and Kim, 2016;Shank and Cutchin, 2016). As it is associated with psychological well-being and resilience, sense of community can have particular relevance for collectivistic cultures experiencing transformation, such as Chinese societies undergoing rapid urban development (Chao and Huang, 2016;Zhang et al, 2017). Mak et al (2009) found that sense of community in Hong Kong was negatively associated with daily hassles and positively with social support.…”
Section: Introductionmentioning
confidence: 99%